Experimental investigation of a hybrid configuration of solar thermal collectors and desiccant indirect evaporative cooling system - Ditta, Allah; Tabish, Asif Nadeem; Mujtaba, M. A.; Amjad, Muhammad; Yusuf, Abdulfatah Abdu; Chaudhary, Ghulam Qadar; Razzaq, Luqman; Abdelrahman, Anas; Kalam, M. A (Frontiers in Energy Research, 2022)
This paper presents the integrated performance of a solar-assisted desiccant dehumidifier along with Maisotsenko cycle (M-cycle) counter flow heat and mass exchanger. This system handles latent load and sensible load separately. The hybrid configuration of solar thermal collectors was analyzed for efficiency of solar collectors and solar fraction. High consumption of fossil fuels, which are already present in a limited amount, is also associated with environmental problems and climate change issues, as these increase the chances of global warming. These issues demand of us to shift towards renewable energy resources. Increase in world energy use results in a number of environmental problems, such as climate change, in addition to global warming and ozone depletion. In building services, HVAC systems are major concerns. To overcome the requirement, conventional air conditioning and vapor compression systems are mainly used for air conditioning, although these also have some environmental problems. Solar thermal applications in combination with other renewable-energy-dependent cooling practices have generated a huge interest towards sustainable solutions, keeping in view several techno-economical, environmental, and climatic advantages. The experimental investigation reveals that the maximum outlet temperature and efficiency of solar thermal collectors was 87°C and 56% respectively. The maximum cooling capacity of the system is evaluated at 4.6 kW.